2022
DOI: 10.3390/cells11091432
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the Tip of the Iceberg: DJ-1 Implications in Cancer Metabolism

Abstract: DJ-1, also called Parkinson’s protein 7 (PARK7), is ubiquitously expressed and plays multiple actions in different physiological and, especially, pathophysiological processes, as evidenced by its identification in neurodegenerative diseases and its high expression in different types of cancer. To date, the exact activity of DJ-1 in carcinogenesis has not been fully elucidated, however several recent studies disclosed its involvement in regulating fundamental pathways involved in cancer onset, development, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 131 publications
0
12
0
Order By: Relevance
“…It should be noted that the covalent, irreversible nature of JYQ-194 may limit its potency as it cannot be recycled upon PARK7 degradation, which possibly lowers its efficacy in an in vivo setting . Despite its limitation, the creation of JYQ-194 PROTAC provides new opportunities for targeting PARK7 in cancer therapy since PARK7 is overexpressed in various types of cancer. ,, …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the covalent, irreversible nature of JYQ-194 may limit its potency as it cannot be recycled upon PARK7 degradation, which possibly lowers its efficacy in an in vivo setting . Despite its limitation, the creation of JYQ-194 PROTAC provides new opportunities for targeting PARK7 in cancer therapy since PARK7 is overexpressed in various types of cancer. ,, …”
Section: Discussionmentioning
confidence: 99%
“… 31 Despite its limitation, the creation of JYQ-194 PROTAC provides new opportunities for targeting PARK7 in cancer therapy since PARK7 is overexpressed in various types of cancer. 1 , 5 , 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of DJ-1 gene can not only be used as a marker for mental cognitive diseases (such as Parkinson's disease, Alzheimer's disease 12 , 13 ), but also participate in the occurrence and progression of various tumors (thyroid cancer 20 , ovarian cancer 41 , colon cancer 14 , 16 , 21 , liver cancer 25 – 31 , lung cancer 22 , 23 , renal clear cell carcinoma 42 , breast cancer 17 ). Since Zhang D et al first found that the expression of DJ-1 is associated with the occurrence of HCC associated with HBV infection 43 , the role of DJ-1 in the proliferation, invasion and metastasis of HCC 25 – 30 , has been paid more and more attention by researchers, and it is regarded as a potential oncogene therapy target for HCC 15 . In this study, we first analyzed the expression level of DJ-1 in TCGA database and clinical HCC tissue samples, and the results showed that the expression of DJ-1 in TCGA database and HCC tissue samples was significantly higher than that of normal tissues and paracancerous tissues, and was closely related to the clinical stage T (T1T2 vs T3T4), pathological grade (I II vs III IV.)…”
Section: Discussionmentioning
confidence: 99%
“…The probable cause of the activation of EMT is due to the activation of the Wnt/β-catenin signalling pathway, which plays a fundamental role in determining the cell fate during early embryonic development along with the regulation of proliferation, and survival and apoptosis ( Liu et al, 2022 ). However, mutation of the Wnt pathway can lead to cancer due to the activation of the multifunctional protein DJ-1 ( Olivo et al, 2022 ). Our current experiment focused mainly on the relationship between Cx43, DJ-1 and EMT responsible for causing more migration in HeLa 43 cells however the mechanism of how DJ-1 activates the Wnt pathway by inhibiting β-catenin and thereby promoting EMT was not further investigated.…”
Section: Discussionmentioning
confidence: 99%